SPARC and GluA1-Containing AMPA Receptors Promote Neuronal Health Following CNS Injury - Jones, Emma V.; Bernardinelli, Yann; Zarruk, Juan G.; Chierzi, Sabrina; Murai, Keith K. (Frontiers in Cellular Neuroscience, 2018)
The proper formation and maintenance of functional synapses in the central nervous system (CNS) requires communication between neurons and astrocytes and the ability of astrocytes to release neuromodulatory molecules. Previously, we described a novel role for the astrocyte-secreted matricellular protein SPARC (Secreted Protein, Acidic and Rich in Cysteine) in regulating α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and plasticity at developing synapses. SPARC is highly expressed by astrocytes and microglia during CNS development but its level is reduced in adulthood. Interestingly, SPARC has been shown to be upregulated in CNS injury and disease. However, the role of SPARC upregulation in these contexts is not fully understood. In this study, we investigated the effect of chronic SPARC administration on glutamate receptors on mature hippocampal neuron cultures and following CNS injury. We found that SPARC treatment increased the number of GluA1-containing AMPARs at synapses and enhanced synaptic function. Furthermore, we determined that the increase in synaptic strength induced by SPARC could be inhibited by Philanthotoxin-433, a blocker of homomeric GluA1-containing AMPARs. We then investigated the effect of SPARC treatment on neuronal health in an injury context where SPARC expression is upregulated. We found that SPARC levels are increased in astrocytes and microglia following middle cerebral artery occlusion (MCAO) in vivo and oxygen-glucose deprivation (OGD) in vitro. Remarkably, chronic pre-treatment with SPARC prevented OGD-induced loss of synaptic GluA1. Furthermore, SPARC treatment reduced neuronal death through Philanthotoxin-433 sensitive GluA1 receptors. Taken together, this study suggests a novel role for SPARC and GluA1 in promoting neuronal health and recovery following CNS damage.